STRATEGI PENGELOLAAN KELAS YANG EFEKTIF DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA KELAS VII MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 5 KOTA JAMBI - Anggreni, Trisna Febriantika; Al-Anwari, Amirul Mukminin (STKIP Pesisir Selatan, 2026)
Class management plays an important role in creating conducive learning processes, especially in the subjects of Moral Faith emphasizing character formation. This research aims to describe effective class management strategies in improving the discipline of class VII E students in Moral Faith subjects at Islamic Junior High Scool Negeri 5 Jambi City. Research methods use a descriptive qualitative approach with data collection techniques through observation, in-depth interviews and documentation. The results of the study showed that teachers use several class management strategies, such as seating arrangements, classroom habits, reward and punishment granting, persuasive communication use, and creating an active and conducive learning atmosphere. However, the supporting factors of the strategy include adequate means and infrastructure, cooperation between teachers and students, as well as support from the school. The inhibitory factors include diverse student characters, lack of learning motivation, as well as class environmental disorders. Overall, the applied classroom management strategy proved to improve student learning discipline, characterized by increasing engagement, attention in learning, as well as punctuality in completing tasks.